Pengaruh Fasilitas Belajar Dan Budaya Organisasi Terhadap Prestasi Belajar Siswa Kelas VI di SDN 32 Bonto Tinggi Kabupaten Pangkep - Gurdi Gurdi; Suwardi Annas; Rego Devilla (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The purpose of this study was to determine the effect of learning facilities and organizational culture on the learning achievement of sixth grade elementary school students. This research is quantitative research with a descriptive approach. Data collection by lift and study documentation. Data analysis used descriptive statistics and inferential statistics. Based on the results of research that has been processed, it shows that learning facilities and organizational culture simultaneously are 60.40% of student achievement, as evidenced by the r-square value of (0.604) and the Fcount value (6.614) which is greater than the F Table value (5.79). It is concluded that there is a significant influence between learning facilities and organizational culture on the learning achievement of sixth grade elementary school students.